Um mapa setorial do emprego e dos salários a partir dos dados da Rais - Claudio Roberto Amitrano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The aim of this paper is to make a sectoral mapping of the labor market between 1995 and 2010, especially from the employment and wage data from the Annual Report of Social Information (Rais) and the General Register of Employed and Unemployed (Caged) of the Ministry of Labour and Employment (MTE), although information from the National Sample Survey (Pnad) and the Monthly Employment Survey (PME), both from IBGE have also been used. The study focused on the analysis of the trajectory of the sectoral composition of employment and employment-product elasticities' sector. Finally a discussion on income inequality in the formal sector of the economy and the impact of sectoral segmentation has on its evolution over the period in question was taken.
Keywords: J01; J21; J31; 330; employment structure; wage inequality; Rais